2021
DOI: 10.3389/fonc.2021.769727
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prognostic Gene Signature Correlated With M2 Macrophage Infiltration in Esophageal Squamous Cell Carcinoma

Abstract: BackgroundEsophageal squamous cell carcinoma (ESCC) is the most common type of esophageal cancer and the seventh most prevalent cause of cancer-related death worldwide. Tumor microenvironment (TME) has been confirmed to play an crucial role in ESCC progression, prognosis, and the response to immunotherapy. There is a need for predictive biomarkers of TME-related processes to better prognosticate ESCC outcomes.AimTo identify a novel gene signature linked with the TME to predict the prognosis of ESCC.MethodsWe c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…C1QC, as important gene for the complement system and thus innate immune response, has been found to be a part of tumor microenvironment of different cancer entities [ 34 , 35 ]. In esophageal squamous cell carcinoma, C1QC was potentially related with prognosis in a bioinformatics analysis [ 36 ]. Therefore, its relation with OSCC development and prognosis appears reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…C1QC, as important gene for the complement system and thus innate immune response, has been found to be a part of tumor microenvironment of different cancer entities [ 34 , 35 ]. In esophageal squamous cell carcinoma, C1QC was potentially related with prognosis in a bioinformatics analysis [ 36 ]. Therefore, its relation with OSCC development and prognosis appears reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, exploiting novel prognostic indicators and therapeutic approaches is particularly crucial. Numerous researchers have made efforts on biomarker-based classifier and obtained encouraging achievements in assessing the survival outcome of EC [ 22 , 23 ]. Nevertheless, these prognostic models are more or less flawed and we need to discover more powerful signature for prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the researchers are focusing on the finding of prognostic factors in ESCC, eventually matched in prognostic scores or signatures. In this regard, Yao J et al recently developed a prognostic gene signature by analyzing 95 samples from the TCGA ESCC cohort [ 31 ]. The study showed that a 10-gene signature (C1QA, C1QB, C1QC, CD86, C3AR1, CSF1R, ITGB2, LCP2, SPI1, and TYROBP) was linked to M2 macrophage in the tumour microenvironment (TME) and poor prognosis in ESCC that expresses those genes (HR: 2.104, p = 0.001).…”
Section: Molecular Biomarkers For Immunotherapymentioning
confidence: 99%